Fatty acids and risk of dilated cardiomyopathy: A two-sample Mendelian randomization study - Zhang, Jiexin; Luo, Qiang; Hou, Jun; Xiao, Wenjing; Long, Pan; Hu, Yonghe; Chen, Xin; Wang, Han (Frontiers in Nutrition, 2023)
Background Previous observational studies have shown intimate associations between fatty acids (FAs) and dilated cardiomyopathy (DCM). However, due to the confounding factors and reverse causal association found in observational epidemiological studies, the etiological explanation is not credible. Objective To exclude possible confounding factors and reverse causal associations found in observational epidemiological studies, we used the two-sample Mendelian randomization (MR) analysis to verify the causal relationship between FAs and DCM risk. Method All data of 54 FAs were downloaded from the genome-wide association studies (GWAS) catalog, and the summary statistics of DCM were extracted from the HF Molecular Epidemiology for Therapeutic Targets Consortium GWAS. Two-sample MR analysis was conducted to evaluate the causal effect of FAs on DCM risk through several analytical methods, including MR-Egger, inverse variance weighting (IVW), maximum likelihood, weighted median estimator (WME), and the MR pleiotropy residual sum and outlier test (MRPRESSO). Directionality tests using MR-Steiger to assess the possibility of reverse causation. Results Our analysis identified two FAs, oleic acid and fatty acid (18:1)-OH, that may have a significant causal effect on DCM. MR analyses indicated that oleic acid was suggestively associated with a heightened risk of DCM (OR = 1.291, 95%CI: 1.044–1.595, P = 0.018). As a probable metabolite of oleic acid, fatty acid (18:1)-OH has a suggestive association with a lower risk of DCM (OR = 0.402, 95%CI: 0.167–0.966, P = 0.041). The results of the directionality test suggested that there was no reverse causality between exposure and outcome (P < 0.001). In contrast, the other 52 available FAs were discovered to have no significant causal relationships with DCM (P > 0.05). Conclusion Our findings propose that oleic acid and fatty acid (18:1)-OH may have causal relationships with DCM, indicating that the risk of DCM from oleic acid may be decreased by encouraging the conversion of oleic acid to fatty acid (18:1)-OH.